Gakkel Ridge basalt melt inclusion and mineral chemistry (IEDA: EarthChem Library)
Analyses of volatile, major, and trace elements for a suite of glasses and melt inclusions from the 85 degrees E segment of the ultra-slow spreading Gakkel Ridge.